The new ecological anthropology. - Kottak, Conrad Phillip (American Antropological Association, 1999)
Older ecologies have been remiss in the narrowness of their spatial and temporal horizons, their functionalist assumptions, and their apolitical character. Suspending functionalist assumptions and an emphasis upon (homeo)stasis, Òthe new ecological anthropologyÓ is located at the intersection of global, national, regional, and local systems, studying the outcome of the interaction of multiple levels and multiple factors. It blends theoretical and empirical research with applied, policy-directed, and critical work in what Rappaport called an ÒengagedÓ anthropology; and it is otherwise attuned to the political aspects and implications of ecological processes. Carefully laying out a critique of previous ecologies by way of announcing newer approaches, the article insists on the need to recognize the importance of culture mediations in ecological processes rather than treating culture as epiphenomenal and as a mere adaptive tool. It closes with a discussion of the methodologies appropriate to the new ecological anthropology